2005
DOI: 10.1016/j.jvs.2005.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Rapid foot and calf compression increases walking distance in patients with intermittent claudication: Results of a randomized study

Abstract: The results of this pilot study show that IPCFC improves walking distance in patients with stable intermittent claudication. A significant increase in ICD and ACD was seen at 4 and 6 months of treatment, respectively, and the improvement was sustained at 1 year. The combination of IPCFC with other treatment such as risk-factor modification and daily exercise may prove useful in patients with peripheral arterial occlusive disease. It may be a useful first line of therapy in patients with disabling claudication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
1
36
0
2
Order By: Relevance
“…However, here, we aimed to give fi rst evidence for long-term ISRT, and, indeed, we showed that walking distance improved with a more than two-fold increase in ICD and ACD in all of the tested PAD patients. Recent studies investigated the effect of diff erent compression devices on PAD patient outcome by focusing on peripheral perfusion and claudication pain [13,14]. Intermittent pneumatic calf and foot compression revealed a signifi cant improvement of the ICD and ACD after a daily treatment of 2 hours for 4 -6 months in a cohort of 30 patients [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, here, we aimed to give fi rst evidence for long-term ISRT, and, indeed, we showed that walking distance improved with a more than two-fold increase in ICD and ACD in all of the tested PAD patients. Recent studies investigated the effect of diff erent compression devices on PAD patient outcome by focusing on peripheral perfusion and claudication pain [13,14]. Intermittent pneumatic calf and foot compression revealed a signifi cant improvement of the ICD and ACD after a daily treatment of 2 hours for 4 -6 months in a cohort of 30 patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigated the effect of diff erent compression devices on PAD patient outcome by focusing on peripheral perfusion and claudication pain [13,14]. Intermittent pneumatic calf and foot compression revealed a signifi cant improvement of the ICD and ACD after a daily treatment of 2 hours for 4 -6 months in a cohort of 30 patients [13]. However, there was no initial examination that evaluated the patient's individual peripheral perfusion status under treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The treadmill was calibrated before the test. The walking test was done according to international treadmill protocols 17,18) .…”
Section: Methodsmentioning
confidence: 99%
“…Because IPC is homebased, this treatment strategy overcomes the major limitations associated with the surgical and noninvasive therapeutic options available for these patients, including low accessibility and unsatisfactory cost-effectiveness (6,17). Clinical trials in stable claudicants indicate that 3 mo of daily IPC application can increase maximal walking distance by ϳ110% (5,9,27), an improvement that is comparable to that obtained by supervised exercise training (17,32). Despite the growing clinical acceptance, the fundamental mechanisms by which IPC therapy promotes clinical benefits remain unclear.…”
Section: Application Of Intermittent Pneumatic Leg Compressions (Ipc)mentioning
confidence: 99%
“…We also evaluated the time course and magnitude of IPC-induced changes in mRNA and protein expression of VEGF, MCP-1, and cytokine-induced neutrophil chemoattractant 1 (CXCL1/CINC-1) in the TA muscle. The second aim was to test the hypothesis that in limbs of chronic bilateral occluded rats, a higher compression frequency would evoke more robust changes in the expression of the aforementioned factors than 3 compressions/min, which is the frequency currently employed in commercially available devices (5,9,17,27). This hypothesis was based on previous results in healthy animals (28), where the higher frequency of compressions had greater effects on the expression of these genes.…”
Section: Application Of Intermittent Pneumatic Leg Compressions (Ipc)mentioning
confidence: 99%